The Fabrication and Characterizations of Coal Briquettes Composed by Charcoal – Clay – Rice Husk Ashes and Adhesive - Sembiring, Manis (Talenta Publisher, 2019)
Coal briquettes are solid materials that can be used as fuels. The composition of this solid fuels are mixed by clay as the ashes binder, rice husks powder as flame additives, and starch flour as adhesive materials. These materials were prepared in different ratio to be mixed homogeneously which are determined accordingly. The fabrication was conducted by mixing methods, and pressed by hydraulic press within 3100 KPa. The results were placed inside an oven to be dried for 24 hours within 85oC of temperature, followed by 24 hours of allowing standing in room temperature. Afterward, the characterizations of the coal briquettes were done by performing density and compressive strength, while the others physical properties such as specific heat, combustion, and purity properties were also tested. The physical properties showed that coal briquettes are flammable and high ignition characteristics. The stability and speed of combustion to fire have continuous and fixed combustion indicated by the presence of solid ashes. The samples suggested that the M1 samples provided fragile ashes with mass loss accounted for 56.33%, and it has the highest specific heat values accounted for 246.66 Kcal/Kg. Meanwhile, the lowest specific heat value was 162.26 Kcal/Kg which was M4 samples with mass loss for 34.53%.